Hidden gene amplifications in aggressive B-cell non-Hodgkin lymphomas detected by microarray-based comparative genomic hybridization - Wessendorf, Swen; Schwaenen, Carsten; Kohlhammer, Holger; Kienle, Dirk; Wrobel, Gunnar; Barth, Thomas FE; Nessling, Michelle; Möller, Peter; Döhner, Hartmut; Lichter, Peter; Bentz, Martin (Oncogene, 2003)
DNA amplifications are important mechanisms for proto-oncogene activation. Comparative genomic hybridization (CGH) to metaphase chromosome preparations has revealed amplifications in 10–20% of B-cell lymphomas (B-NHL). We analysed a series of 16 aggressive non-Hodgkin lymphomas by the new approach termed Matrix-CGH (M-CGH) using genomic DNA microarrays as hybridization target. For M-CGH, a dedicated B-cell lymphoma chip was constructed containing 496 genomic targets covering oncogenes, tumor suppressor genes as well as chromosome regions frequently altered in B-NHL. In 10 of 16 samples a total of 15 DNA amplifications were identified. The amplicons included BCL2, REL, CCND1, CCND2, JAK2, FGF4 and MDM2 . Four of the 15 amplifications remained undetected by chromosomal CGH. The respective amplicons mapped to bands 2p13, 9p13–p21 and 12q24 and, were confirmed by fluorescence in situ hybridization. Furthermore, for four genomically amplified genes real-time quantitative reverse transcription polymerase chain reaction revealed elevated mRNA expression levels. These data show the superior diagnostic sensitivity of the newly developed diagnostic tool. As only a small portion of the genome (approximately 1.5%) has been analysed by the present DNA array, it is likely that gene amplifications are much more common in aggressive lymphomas than previously assumed.